Creative Users, Social Networking, and New Models of Publishing - Ren Xiang (Cultural Science)
This paper reviews the changing landscape of the publishing industry, which is being reshaped by dynamics of user co-creation, social networking and open licencing. It briefly touches on possible research themes associated with disruptive changes in the world’s oldest media/creative industry, particularly under the umbrella of “Cultural Science”. Two new models of publishing are discussed: literary self-publishing in China and open innovations in academic publishing. It argues that evolution in the publishing industry goes beyond “digital publishing” towards “new publishing in a digital world”, demanding new models serving population-wide creativity and open knowledge communication.